An Analysis of the Causes of Damage to Nata de Coco in the Fermentation Process - Alfarisy, Moh; Rahmadhia, Safinta Nurindra (Universitas Ahmad Dahlan, 2021)
Acetobacter xylinum greatly contributes to the fermentation process of nata de coco. It converts glucose in coconut water into cellulose slabs. The slabs turn into clear white and solid in form, called nata. This analysis is aimed to identify types and causes of damage to nata de coco in the fermentation process. Observation of the criteria of raw materials, cooking process, the making of an Acetobacter xylinum starter, pouring the medium into the stray, and the harvesting process of nata slabs was carried out in the fermentation process. Data collected were analyzed, and research problems were solved using the Fishbone diagram. Several methods applied in data collection were observation, interview, hands-on practice, documentation, and literature study. The results demonstrated some types of damage to nata slabs in the fermentation process, e.g., fungal contamination and defective, watery, and fibrous nata.